2007
DOI: 10.1038/sj.jcbfm.9600344
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia—Ischemia Preferentially Triggers Glutamate Depletion from Oligodendroglia and Axons in Perinatal Cerebral White Matter

Abstract: Ischemia is implicated in periventricular white matter injury (PWMI), a lesion associated with cerebral palsy. PWMI features selective damage to early cells of the oligodendrocyte lineage, a phenomenon associated with glutamate receptor activation. We have investigated the distribution of glutamate in rat periventricular white matter at post-natal day 7. Immuno-electron microcopy was used to identify O4( + ) oligodendroglia in control rats, and a similar approach was employed to stain glutamate in these cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 51 publications
2
66
0
Order By: Relevance
“…Thomas et al (2004) also demonstrated a high resting intracellular glutamate levels in oligodendrocytes that was elevated following ischemia, suggesting both effective glutamate uptake under normal conditions and the absence of uptake reversal during ischaemia. It is not known how [Na + ] i , pH i and membrane potential are affected by ischemia in these cells but it would appear that the conditions are not met for significant reversal of glutamate uptake in this preparation (but see Back et al 2006). The current findings suggest that glutamate release from axons via reverse transport is a potentially important factor in excitotoxic (Dewar et al, 2003;Wilke et al, 2004) and non-excitotoxic (Oka et al, 1993) white matter damage during ischemia.…”
Section: Discussionmentioning
confidence: 63%
“…Thomas et al (2004) also demonstrated a high resting intracellular glutamate levels in oligodendrocytes that was elevated following ischemia, suggesting both effective glutamate uptake under normal conditions and the absence of uptake reversal during ischaemia. It is not known how [Na + ] i , pH i and membrane potential are affected by ischemia in these cells but it would appear that the conditions are not met for significant reversal of glutamate uptake in this preparation (but see Back et al 2006). The current findings suggest that glutamate release from axons via reverse transport is a potentially important factor in excitotoxic (Dewar et al, 2003;Wilke et al, 2004) and non-excitotoxic (Oka et al, 1993) white matter damage during ischemia.…”
Section: Discussionmentioning
confidence: 63%
“…The tissue samples were handled as reported previously (39). Briefly, brain section was quickly cut into 1 mm cubes, immersion-fixed with 2.5% glutaraldehyde in 0.1 mol/L phosphate buffer (pH 7.4) overnight at 4°C and fixed in 1% buffered osmium tetroxide.…”
Section: Transmission Electron Microscopic Examinationmentioning
confidence: 99%
“…In adult WM, ischemic injury is mediated by AMPA/kainate receptors (Tekkök and Goldberg, 2001). During ischemia, axons and OLs release glutamate, resulting in activation of WM glutamate receptors and cellular injury (Li et al, 1999;Back et al, 2007). Does glutamate injure axons directly?…”
Section: Mechanisms Of Axonal Degenerationmentioning
confidence: 99%